2014
DOI: 10.1007/s11103-014-0261-2
|View full text |Cite
|
Sign up to set email alerts
|

De novo sequencing and analysis of the lily pollen transcriptome: an open access data source for an orphan plant species

Abstract: Pollen grains of Lilium longiflorum are a long-established model system for pollen germination and tube tip growth. Due to their size, protein content and almost synchronous germination in synthetic media, they provide a simple system for physiological measurements as well as sufficient material for biochemical studies like protein purifications, enzyme assays, organelle isolation or determination of metabolites during germination and pollen tube elongation. Despite recent progresses in molecular biology techn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 85 publications
1
20
0
Order By: Relevance
“…In Arabidopsis, more than 800 transporter transcripts have been identified in pollen using the ATH1 mRNA microarray (Pina et al, 2005;Bock et al, 2006), and this overrepresentation is confirmed by RNA sequencing in Arabidopsis and lily (Loraine et al, 2013;Lang et al, 2015). This is perhaps one of the reasons why PTs have been widely explored in recent years for phenotyping an increasing repertoire of channels, transporters, and pumps, rendering the vegetative cell of the PT likely one of the best studied cells in plants in terms of ion dynamics.…”
Section: Pollen Tubes As a Tailored Model For Studying Ion Dynamics Amentioning
confidence: 95%
See 2 more Smart Citations
“…In Arabidopsis, more than 800 transporter transcripts have been identified in pollen using the ATH1 mRNA microarray (Pina et al, 2005;Bock et al, 2006), and this overrepresentation is confirmed by RNA sequencing in Arabidopsis and lily (Loraine et al, 2013;Lang et al, 2015). This is perhaps one of the reasons why PTs have been widely explored in recent years for phenotyping an increasing repertoire of channels, transporters, and pumps, rendering the vegetative cell of the PT likely one of the best studied cells in plants in terms of ion dynamics.…”
Section: Pollen Tubes As a Tailored Model For Studying Ion Dynamics Amentioning
confidence: 95%
“…(Cheung and Wu, 2007;Michard et al, 2009;Qin and Yang, 2011;Hepler, 2016). On the other hand, their study is backed up by extensive databases on transcriptomics and proteomics on practically all of its biological contexts (Honys and Twell, 2003;Pina et al, 2005;Borges et al, 2008;Qin et al, 2009;Boavida et al, 2011;Mayank et al, 2012;Pertl-Obermeyer et al, 2014;Lang et al, 2015). All these features define a unique cell type so evolutionarily streamlined to fast growth and sperm delivery (Williams, 2008) that it remained basically conserved as the only gametophyte developmental end product for male function since the Cretaceous (Rudall and Bateman, 2007).…”
Section: Pollen Tubes As a Tailored Model For Studying Ion Dynamics Amentioning
confidence: 99%
See 1 more Smart Citation
“…In non-model organism's studies in particular, de novo transcriptome sequencing is powerful and cost-effective. Many metabolic pathways, physiological processes, and growth and development mechanisms of non-model plant have been revealed by de novo transcriptome sequencing (Wu et al, 2014;Lang et al, 2015). The analysis of differentially expressed genes based on transcriptomic data from several samples is a powerful tool for revealing the biological mechanisms underlying differences among individuals (Lou et al, 2014;Liu et al, 2015;Shi et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Several dedicated investigations for different stages and cell types representing pollen are available (Bokvaj et al 2015;Chettoor et al 2014;Davidson et al 2011;Fasoli et al 2012;Haerizadeh et al 2009;Hafidh et al 2012;Hobo et al 2008;Hollender and Kang 2014;Lang et al 2015;Ma et al 2008;Sanetomo and Hosaka 2013;Suwabe et al 2008;Wei et al 2010). Indeed, gene expression studies by RNA-seq permitted to identify around 150 different pollen-expressed genes in different plant species associated with a range of different functions, including cell wall metabolism, cytoskeleton and signaling (Honys and Twell 2003;Palanivelu and Tsukamoto 2012;Rutley and Twell 2015).…”
Section: Next Generation Sequencing (Ngs) Datamentioning
confidence: 99%